Comparison of peri‐implant clinical outcomes of digitally customized and prefabricated abutments: A systematic review and meta‐analysis. (2nd February 2021) - Raee, Amir; Alikhasi, Marzieh; Nowzari, Hessam; Djalalinia, Shirin; Khoshkam, Vahid; Moslemi, Neda
Abstract: Background: Digitally customized abutments are increasingly used in contemporary implant prosthodontics. Purpose: This systematic review and meta‐analysis aimed at comparing the peri‐implant clinical outcomes of digitally customized and prefabricated abutments. Materials and methods: The search strategies included electronic databases (PubMed, Embase, Scopus, and Cochrane clinical trials database) and related journals up to September, 2020. A qualitative and quantitative synthesis was performed on data extracted from the included studies. Results: Three RCTs (number of patients = 120; number of dental implants = 120) and two prospective cohort studies (number of patients = 144; number of dental implants = 144) with one to three‐year follow‐up periods were included. The quantitative analyses did not demonstrate a significant difference between digitally customized and prefabricated abutments for peri‐implant pocket depth ( P = 0.62), plaque index ( P = 0.67), bleeding on probing ( P = 0.43), keratinized mucosa width ( P = 0.75), and pink aesthetic score ( P = 0.30) at one‐year follow‐up visit. The qualitative analyses for marginal bone level change, calculus accumulation, implant survival rate, implant success rate, white aesthetic score, and patient‐reported outcomes did not demonstrate a significant difference between two groups during 1 to 3‐year follow‐up visits. Conclusion: The current data do not provide evidence of significant differences between two abutment fabrication methods in terms of peri‐implant clinical outcomes within short‐term period (CRD42020170807).